Peran Pertanian Terhadap Pendapatan Rumah Tangga Petani Subak Sembung Kota Denpasar Saat Pandemi Covid-19 - Kadek Ratih Maha Asri; Dwi Putra Darmawan; Gede Mekse Korri Arisena (Fakultas Pertanian, Universitas Udayana, 2021)
Urban agriculture has an important role in providing a source of family income. One of the subaks in urban areas that is still producing is the Sembung Subak, which is located in Peguyangan Village, North Denpasar District. The purpose of this study was to determine the profile of urban agricultural enterprises in Subak Sembung, Denpasar City, to determine farm income in urban agriculture and farm households in Subak Sembung and to determine the role of farming in urban agriculture on farm household income. The samples of this study were 66 farmers who were taken from 8 munduk in Subak Sembung. This type of research is descriptive quantitative. The variables observed in this study were cash receipts, cash and non-cash variable costs, fixed costs and equipment depreciation costs. The results showed that most of the farmers were still of productive age with the main job as farmers. The average farm income in Subak Sembung for 2020 was IDR 27,082,103/year. Based on the R/C value obtained> 1, it can be concluded that all commodities cultivated by farmers are efficient. The average farm household income is IDR 51,606,864/year. The contribution given from farming to total farm household income is 46.9%, it can be concluded that agriculture in Subak Sembung plays a role in household income. During the Covid-19 pandemic, the income of farmers who cultivated rice in Subak Sembung did not experience significant changes, while for vegetable farmers, there was a change due to decreased purchasing power.